2015
DOI: 10.1001/jamaoncol.2015.0203
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Expected Costs and Benefits of Granting Access to New Treatments on the Basis of Progression-Free Survival in Non–Small-Cell Lung Cancer

Abstract: The value of providing access to new treatments on the basis of surrogate end points, and PFS in particular, likely varies considerably. Payers and clinicians should carefully consider how to use PFS data in balancing potential benefits against costs in each particular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Finally, a recent study suggests that approving new drugs based on surrogates (even inaccurate ones) may provide a greater benefit for society than waiting for OS data. 101 The authors found favorable societal benefits for approving non-small-cell lung cancer (NSCLC) drugs with PFS benefits of 3 months or more. This occurred despite the fact that the authors noted a poor correlation (as we also did in Table 1) between net mean PFS and OS in NSCLC cancer (r = 0.56).…”
Section: Limitationsmentioning
confidence: 99%
“…Finally, a recent study suggests that approving new drugs based on surrogates (even inaccurate ones) may provide a greater benefit for society than waiting for OS data. 101 The authors found favorable societal benefits for approving non-small-cell lung cancer (NSCLC) drugs with PFS benefits of 3 months or more. This occurred despite the fact that the authors noted a poor correlation (as we also did in Table 1) between net mean PFS and OS in NSCLC cancer (r = 0.56).…”
Section: Limitationsmentioning
confidence: 99%
“…In making drug approval decisions, the costs and benefits of granting earlier approval based on surrogate end-points must be weighed and, often (e.g. in many cancer types and LIMITATIONS OF TRADITIONAL HTA type 2 diabetes), the expected benefits outweigh the costs 15,70 . HTAs often use information on adverse events observed in clinical trials to infer real-world and long-run side-effects.…”
Section: Lack Of Long-run Evidencementioning
confidence: 99%
“…Given the challenges in determining OS, particularly in the presence of crossover, additional efficacy end points, such as progression-free survival (PFS), are frequently used in clinical trials in oncology. There is an ongoing debate whether PFS is a useful surrogate for OS in oncology [8,9]. Although PFS may be accepted as a primary end point in oncology trials by regulatory agencies in certain settings and under certain conditions [7], reliable and unbiased OS estimates are still likely to be required for health technology assessments [10].…”
Section: Introductionmentioning
confidence: 99%